The imapct of Americorps service on volunteer participants: results from a 2-year study in four Western states - Simon, Christopher A.; Wang, Changhua (2002)
Earlier evaluation of Americorps have approached the study of program effects in two general ways. Cost-benefit studies indicate that in select projects the program produces a substantial net benefit. Qualitative studies conclude that the program has a substantial impact on the strength of communities, provides an influx of social capital, and solves unmet human needs. The authors' analysis focuses on the impact of AmeriCorps on the volunteer members. In a 2-year preservice-postservice analysis they found that the members become more active in community groups. AmeriCorps participation may strengthen social capital - participation parallels a significant value shift among participants. - Reproduced.
Keywords: Corporations - United States; Corporations